The Role of Market Orientation in Mediation the Impact of Entrepreneurship Orientation on Company Performance and Competitive Advantage - Laura Amelia Triani; Yulia Hendri Yeni (Journal of Social Research, 2023)
The purpose of this research is to see how the SME Orientation Strategy is implemented in West Sumatra. The strategy uses two parameters, namely entrepreneurial orientation and market orientation. The focus of this research objective is to analyze the role of market orientation in mediating the effect of entrepreneurial orientation on company performance and competitive advantage in SMEs, especially the food industry in Rumah Makan Minang, West Sumatra. The subjects of this study were restaurants registered with the West Sumatra BPS which were surveyed by the Googlemaps team in 11 cities. The sample of this research comes from restaurant owners. Data collection was carried out by distributing 173 questionnaires to restaurant owners or management. The data collection process was carried out by a team of five people who had experience and received training and understanding of the questions in the survey. The data analysis technique is SEM (Structural Equation Model) with the SmartPLS 3.2.8 professional application program. This study found that market orientation plays a role in mediating the influence of entrepreneurial orientation on company performance, but it is not proven to play a role in mediating the influence of entrepreneurial orientation on competitive advantage in Minang Restaurant MSME in West Sumatra. Other indicators will be discussed in this article.